Response to Plasmapheresis Measured by Angiogenic Factors in a Woman with Antiphospholipid Syndrome in Pregnancy - Karoline Mayer-Pickel; Sabine Horn; Uwe Lang; Mila Cervar-Zivkovic (Case Reports in Obstetrics and Gynecology)
An imbalance of angiogenic and antiangiogenic placental factors such as endoglin and soluble fms-like tyrosine kinase 1 has been implicated in the pathophysiology of preeclampsia. Extraction of these substances by plasmapheresis might be a therapeutical approach in cases of severe early-onset preeclampsia. Case Report. A 21-year-old primigravida with antiphospholipid syndrome developed early-onset preeclampsia at 18 weeks’ gestation. She was treated successfully with plasmapheresis in order to prolong pregnancy. Endoglin and sflt-1-levels were measured by ELISA before and after treatment. Endoglin levels decreased significantly after treatment (p < 0.05) and showed a significant decrease throughout pregnancy. A rerise of endoglin and sflt-1 preceded placental abruption 4 weeks before onset of incident. Conclusion. Due to the limited long-term therapeutical possibilities for pregnancies complicated by PE, plasmapheresis seems to be a therapeutical option. This consideration refers especially to pregnancies with early-onset preeclampsia, in which, after first conventional treatment of PE, prolongation of pregnancy should be above all.